Preventing Corruption in Government Bodies Under the Laws of Muslim and European Countries in the Contemporary Era - Tetiana Kolomoiets; Denys Chyzhov; Andriy Osaulenko; Serhii Kushnir; Vyacheslav Krahlevych (MILRev: Metro Islamic Law Review, 2026)
This study examines mechanisms for preventing corruption in contemporary governance through a comparative analysis of Islamic and European legal frameworks. The research aims to identify normative principles, institutional structures, and regulatory approaches that enhance anti-corruption effectiveness in state authorities, highlighting the influence of religious and secular legal norms. A comparative legal method was employed to analyse primary legal sources, institutional models, financial control systems, and sanctioning approaches. In Muslim countries, Sharia principles are integrated with national legislation to regulate anti-corruption measures, as seen in the United Arab Emirates, where strict criminal sanctions for bribery are reinforced by digital control of public services. In contrast, European countries, exemplified by France under the Sapin II Law (2016), implement mandatory corporate compliance programs within a secular legal framework and emphasise institutional transparency and accountability. Statistical indicators, including the Transparency International Corruption Perception Index for 2020–2025, were examined alongside the operational practices of specialised anti-corruption bodies. Findings reveal that the effectiveness of anti-corruption measures depends not only on sanction severity but also on the comprehensiveness of legal regulation, institutional independence, and societal intolerance for corruption. Muslim countries achieve notable results when religious principles are combined with modern management tools, while European countries excel through systematic preventive policies, transparency, and accountability mechanisms. The study highlights both commonalities and divergences between the two legal models and outlines opportunities to adapt selected elements of foreign anti-corruption practices to the Ukrainian context. This comparative approach contributes to the scholarly understanding of how legal, institutional, and cultural factors jointly shape corruption prevention, offering insights for policymakers seeking to strengthen governance frameworks in diverse socio-legal settings.